Lavandula dentata AND Lavandula angustifolia IN VITRO ORGANOGENESIS - DE BONA, CLAUDINE MARIA; REINHART, VANESSA; BIASI, LUIZ ANTONIO; ZANETTE, FLAVIO (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2016)
Lateral buds (0.5 mm), nodal segments (1 cm), shoot tips (1 mm) and shoot apex (0.25 mm) of english lavender (Lavandula angustifolia Miller) and French lavender (Lavandula dentate L.) were placed on MS culture medium. After in vitro establishment, nodal segments of L. angustifolia containing two leaves were transferred to culture medium with different combinations of 6-benzylaminopurine (BAP) and gibberellic acid (GA3 ) concentrations to induce in vitro organogenesis. After two months, the number and length of formed shoots, the percentage of shoots rooted, shoots with callus and the survival of the shoots were recorded. Shoot apex and lateral buds were considered better explants for in vitro establishment. Better multiplication rate, callus formation and survival percentage were obtained with the 10 mg L-1 BAP combined with 0.5 mg L-1 GA3 , while the lower survival percentage and callus formation occurred on media without regulators (control) for L. angustifolia. Growth of shoots from L. dentata in the applied conditions was not satisfactory.